The Right of Workers with Disabilities: Legal Instrument and Challenges in Indonesia - Muh. Arief Syahroni; Abdullah Fikri; Eka Nanda Ravizki (Universitas Ekasakti, 2024)
Nowadays, people with disabilities still experience various acts of discrimination. For example, mainly constrained by the requirements of